The Contribution of Argentine Neurologists to the Description of Infantile Epileptic Spasms Syndrome and Related Epileptic and Nonepileptic Neurological Conditions - Espeche, Alberto; Valenzuela, Gabriela Reyes; Caraballo, Roberto (Journal of Pediatric Epilepsy, 2023)
In the latest report of the International League against Epilepsy Task Force on Nosology and Definitions on the methodology for classification of epilepsy syndromes, the term infantile epileptic spasms syndrome (IESS) was chosen for what were previously called infantile spasms, including West syndrome and infantile epileptic spasms without hypsarrhythmia.Different Argentine groups have contributed to the description of IESS and related epileptic and nonepileptic syndromes. Here we aimed to review studies by different Argentine authors that contributed to the development of the definitions of IESS and its most important benign differential diagnosis.In 1949, Vazquez and Turner from Argentina first recognized a clinical-electroencephalographic correlate of the entity described by Dr. West defining the triad of epileptic spasms, diffuse paroxysmal cerebral dysrhythmia, and psychomotor impairment. Subsequently, in 1976 Fejerman first reported 10 neurologically normal infants with recurrent spells that resembled epileptic spasms. As neurological status, electroencephalogram (EEG), and outcomes were normal, these infants were clearly different from those with West syndrome or epileptic spasms without hypsarrhythmia.Since 2003, Caraballo et al have published different series of patients with epileptic spasms in clusters without hypsarrhythmia occurring in infancy. Before the onset of the epileptic spasms in clusters, these infants were often normal and they had focal or generalized EEG abnormalities.Publication in local journals in languages other than English may lead to the loss of important data found by colleagues from different geographic areas. Therefore, this should be followed by publication in English in peer-reviewed journals.
Keywords: Argentina; epileptic spasms; Fejerman; infantile; nonepileptic; West syndrome